The Association of Physical Activity and Healthy Eating Behaviours with Mental Health among Adolescents Aged 13-15 in Indonesia - Rezky Aulia Yusuf; Nurul Awalia (CV. Global Health Publication, 2025)
This quantitative cross-sectional study aimed to analyze the influence of balanced nutrition behavior, halal food consumption, prayer habits, physical activity, and sedentary behavior on adolescent mental health and academic achievement. The study involved 249 students aged 13–17 years from SMPN 17 Makassar, using self-administered questionnaires and random sampling. Data were analyzed through univariate, bivariate, and multivariate (Binary Logistic Regression) methods using SPSS 20.0. The findings showed that unbalanced nutrition behaviors significantly affected mental health and academic performance. Adolescents who felt hungry due to insufficient food intake were more likely to feel bored (OR 1.78, p=0.04) and have difficulty completing tasks (OR 2.52, p=0.006). Not consuming fruits and vegetables and frequently eating instant noodles were also associated with low academic scores. The consumption of haram food or drinks and the lack of fardhu or sunnah prayers were linked to feelings of loneliness, anxiety, and lower school grades (OR 3.17, p=0.041). Physical inactivity and sedentary behavior were also significantly correlated with loneliness and academic difficulties. In conclusion, unhealthy lifestyle behaviors independently contribute to poor mental health and low academic achievement. Therefore, school- and family-based interventions are essential to promote healthy, active, and faith-based lifestyles among adolescents.